IndentifyingMaqasid al-Qur’an: A Critical Analysis Of Rashid Riaz’sviews - Islam, Tazul; Khan, Israr Ahmad (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
This articleexaminesMuÍammadRashid Rida’s (1865-1935 C.E.) views of Maqasid al-Qur’an.Rida’s work on this subject is one of a few rear pieces that comprehensively deal with this emerging distinctive concept of understanding the Qur’Énic discourse. Thus, it is significant to view RiÌÉ’s insight and contribution to this subject.This article presents a critical analysis of the ten main objectives of the Qur’an that he dealt with in his book al-WaÍy al-MuÍammadÊ as well as TafsÊr al-ManÉr. This study mainly explores the methodological and logical strength of RiÌÉ’s identification of objectives of the Qur’an.